(untitled) (Damascus University Journal of agriculture sciences, 2023)
The study included eight types of dried fruits by sugar (apples, pears, peaches, orange, bitter orange, figs, cacti and eggplant) sold in Local market, were conducted some chemical and microbiological tests on samples, which showed higher pears samples of the moisture content of the (38%), while the fruits of candied eggplant shown a remarkable increase in the pH (6.11), and the highest content of total sugars reached (62.63 %) on a dry weight basis in the candied apples. Candied apple samples also excelled in the content of total phenols (6.35 mg galic acid / 100 g). The study found that the total count of bacteria in all studied species of dried fruit was under 1 × 102, in addition to contamination with bacteria E.coli and yeast and perhaps this is due to the method of manufacturing and supply at the sales, which may not take into account the often health conditions, while samples were free of bacteria Staph. aureus.